MUSYARAKAH, MUDHARABAH DAN PERTUMBUHAN SEKTOR RIIL - Hakiem, Hilman; Waluyo, Desi Silfiaratih (Al-Infaq: Jurnal Ekonomi Islam, 2011)
Indonesia's economic growth declined in the period 2004-2006. This is caused by too much focus on strengthening the monetary policy, otherwise the real sector less attention. As of May 2006, the bank funds are not channeled into the real sector reached Rp 393 trillion, which is then reinvested in the financial sector. The contradiction of real-monetary sector was due to the high interest rate policy of Bank Indonesia. On the one hand, this policy can reduce inflation, but on the other hand will result in the real sector become slow. This condition requires immediate implementation of an integral and gradual system of Islamic banks as a solution to solving the problem. This paper aims to describe how Islamic banks, through the scheme musyarakah and mudharabah, can improve the real sector growth in the context of overcoming the economic problems of Indonesia.